NAVIGATING THE INFLUENCE OF MARKETING ORIENTATION ON UNIVERSITY PERFORMANCE - MOKOENA, Aubrey Bakae; MAFINI, Chengedzai; DHURUP, Manillal (Studia Universitatis Babeș-Bolyai Oeconomica, 2015)
This study is part of a broad stream of continuing research examining market orientation within higher education and its potential impact on university performance. The study examined the influence of marketing orientation on the performance of South African universities. The sample consisted of 507 academics who were conveniently selected from six universities of technology, located in various provinces of South Africa. Seven marketing orientation elements, namely, market intelligence generation, inter-functional coordination, customer orientation, market intelligence dissemination, intelligence response design, intelligence response implementation and interdepartmental dynamics that exert an impact on university performance were identified using the exploratory factor analysis technique. A Pearson Correlation analysis revealed positive and significant associations between all seven market orientation elements and university performance. Mean score ranking of the seven elements showed that intelligence response design was the most important market orientation element. Subsequent multiple regression analysis revealed that inter-functional coordination, customer orientation, market intelligence dissemination, and intelligence response design predicted university performance. Using the results of this study, marketing practitioners in universities may be able to address university performance challenges by applying a right mix of the seven marketing orientation dimensions examined in this study. The results of this study can be used to develop appropriate marketing strategies that are useful in the diagnosis and rectification of performance challenges in universities. JEL classification: M31, I23